Paternal grandfather’s access to food predicts all-cause and cancer mortality in grandsons - Denny Vågerö; Pia R. Pinger; Vanda Aronsson; Gerard J. van den Berg (Nature Communications, 2018)
Nutritional experience can have phenotypic consequences in subsequent generations, as is evident from studies in animals and plants. Here, Vågerö et al. find in a large three-generation cohort that access to food in the paternal grandfather associates with all-cause and cancer mortality in male grandchildren.